Differences in syntenic complexity between Medicago truncatula with Lens culinaris and Lupinus albus - Phan, H.; Ellwood, Simon; Ford, R.; Thomas, S.; Oliver, Richard (2006)
Orthologous markers transferable between distantly related legume species allow for the rapid generation of genetic maps in species where there is little pre-existing genomic or EST information. We are using the model legume Medicago truncatula Gaertn. to develop such markers in legumes of importance to Australian agriculture. This will enable the construction of comparative genetic maps, help to determine patterns of chromosomal evolution in the legume family, and characterise syntenic relationships between M. truncatula and cultivated legumes. This information can then be used to identify markers that are tightly linked to the genes of interest, candidate gene(s) for a trait, and expedite the isolation of such genes. Among the Papilionoideae, we compared ESTs from the phylogenetically distant species, M. truncatula, Lupinus albus and Glycine max, to produce 500 intron-targeted amplified polymorphic markers (ITAPs). In addition to 126 M. truncatula cross-species markers from Department of Plant Pathology, University of California (USA), these markers were used to generate comparative genetic maps of lentil (Lens culinaris Medik.) and white lupin (Lupinus albus Linn.). Our results showed that 90% of the ITAPs markers amplified genomic DNA in M. truncatula, 80% in Lupinus albus, and 70% in Lens culinaris. The comparative map of Lens culinaris was constructed based on 79 ITAP markers. The Lupinus albus comparative map was developed from 105 gene-based markers together with 223 AFLP markers. Although a direct and simple syntenic relationship was observed between M. truncatula and Lens culinaris genomes, there is evidence of moderate chromosomal rearrangement. This may account for the different chromosome numbers in the two species. A more complicated pattern among homologous blocks was apparent between the Lupinus albus and M. truncatula genomes.